Rain attenuation for 5G network in tropical region (Malaysia) for terrestrial link - Ulaganathen, Kesavan; Abdul Rahman, Tharek; Islam, Rafiqul; Abdullah, Khaizuran (Institute of Electrical and Electronics Engineers Inc., 2018)
Millimeter wave (mm Wave) is today's breakthrough frontier for emerging wireless mobile cellular networks, wireless local area networks, personal area networks, and vehicular communications. In the near future, mm Wave products, systems, theories, and devices will come together to deliver mobile data rates thousands of times faster than today's existing cellular and Wi Fi networks for an example from the era of 3G,4G towards 5G mobile communication near future. This paper presents studies on rain attenuation at 6 GHz and 28 GHz, which is widely used for local multipoint distribution service deployment by using the measured and prediction methods for terrestrial microwave links point to point in tropical regions. In this paper, discussion and comparison of five different reduction factor models have been presented. Several models have been proposed by researchers to account for the horizontal variation of rain fall. However of ITU-R model, revised Moupfouma model, revised Silva Mello model, Abdul Rahman model and Lin model mostly been used for rain attenuation predictions in tropical regions. The objective of these studies to identify rain attenuation using prediction model for 5G network in tropical region for country like Malaysia. This study will provide useful information for researchers by understanding and good considerations in rain attenuation predictions for a terrestrial link operating frequency at lower and higher operating frequencies in a tropical region. At the end of the analysis, it was found the all the five models predicts rain attenuation at lesser than 1 dB and 11 dB for operating microwave frequency at 6 GHz and 28 GHz for 5G Network, This findings will useful for future 5G network designers to consider the effect of rain impairments especially in tropical region.